The relationship between safety training and safety behavior among postmen rider in Pos Malaysia headquarter. - Appanah, Nagamah (2019)
Organization safety at the workplace reflects from employee’s attitude and behavior. Safety behavior plays a crucial role in accident prevention and safety culture development. This study aims to examine the relationship between safety training and safety behavior among postmen. Using a self- administered questionnaire, the survey involves 100 postmen rider who is working in Pos Malaysia Headquarter. The raw data was analyzed by SPPS version 19, and descriptive and inferential analysis was conducted to fulfill the objective of the study. Regression analysis revealed that there is a significant relationship between safety training and safety behavior. Furthermore, safety compliance which is one of the dimension under safety behavior has significant relationship towards safety training. However, it is not significant against safety participation which is another dimension under safety behavior.